La razón de Estado en la política religiosa de los reyes Aqueménidas: ¿tolerancia o intolerancia religiosa? - Campos Méndez, Israel (Gerión. Revista de Historia Antigua, 2006)
Two words would summarize what characterized the religious policy during the two centuries of the Achaemenid Empire: tolerance and party utilization. Inside what it seems to have been a programmatic line, Achaemenid kings had an initial attitude of acceptance of all the religious practices along their territorial conquests. The religious panorama of the Achaemenid Empire is defined by a polytheism generalized, in close relation with the heterogeneous character of its populations and with independence of the existence of an official religion. The reason of state and the political interest occupy, therefore, a central role for understanding why it was not acted of forceful form against the practical rituals of the towns that were submitted.